Body mass index and penile cancer incidence: results from a Norwegian cohort study of 829,081 men - Dagfinn Aune; Marie Nordsletten; Tor Åge Myklebust; Trude Eid Robsahm; Bjørn Steen Skålhegg; Tom Mala; Sheraz Yaqub; Usman Saeed (BMC Urology)
Abstract Background A few previous studies have suggested a possible association between adiposity and increased risk of penile cancer, however, the evidence is to date limited for this rare cancer. We investigated the association between body mass index (BMI) and penile cancer risk in a large Norwegian cohort. Methods The analyses included 829,081 men aged 16–75 years at baseline in 1963–1975. Multivariable Cox regression analyses were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for the associations between BMI and penile cancer incidence. Results A total of 725 incident penile cancer cases occurred during 25.6 million person-years of follow-up. Compared to men with BMI 18.5-<25, the HRs (95% CIs) of those with a BMI of 15-<18.5, 25-<30, and ≥ 30 were 0.45 (0.15–1.41), 1.14 (0.97–1.33) and 1.63 (1.20–2.22), respectively, and the HR was 1.26 (1.12–1.42) per 5 kg/m2 increase in BMI. When the obese category was further subdivided in grade 1 (BMI 30-<35) and grade 2 obesity (≥ 35), the respective HRs were 1.52 (1.10–2.10) and 3.28 (1.46–7.35, ptrend<0.001). The positive association persisted in sensitivity analyses excluding the first 5 years of follow-up. The association between BMI in early adulthood and penile cancer risk was less precise (1.23, 0.91–1.65 per 5 kg/m2, n = 143 cases) and for BMI and early-onset penile cancer was null (1.03, 0.51–2.06 per 5 kg/m2, n = 27 cases). Conclusion High BMI is associated with increased risk of penile cancer. Further studies are needed to investigate the potential underlying mechanisms.